An Evaluation of Short-term Mesocarnivore Control for Increasing Hatch Rate in Northern Bobwhites - Eddie K. Lyons; Jason Frost; Dale Rollins; Cody Scott (National Quail Symposium Proceedings, 2017)
We evaluated the efficacy of short-term trapping on scent-station visitation rates for some nest predators and survival of artificial nests with chicken eggs at 4 sites in west Texas from 1998-2001. Trapping of predators was conducted with cage traps for 30 days just prior to nest initiation (mid-May through mid-June) at a trap density of 1 trap/20 ha. Each site included a treatment (trapped) and control (non-trapped) area that comprised approximately 250 ha. Scent stations were employed before and after trapping to assess impacts of trapping on predator activity/abundance. Simulated nests (using 3 chicken eggs) were established 1-2 days after trapping ended, and monitored weekly to estimate visitation rate. We removed an average of 69 mesomammals per year (n = 274 across all sites), within a 30-day-trapping period. We detected no consistent declines in scent-station visitation rates of target species before or after trapping. We did not detect an increase in survival of artificial nests. We conclude that short-term trapping efforts on small areas used in this study did not reduce the overall predator community enough to affect scent-station visitation rates or survival of artificial nests.
Keywords: Colinus virginianus; mesomammal abundance; nesting success; northern bobwhite; predator control; Rolling Plains; Texas